Stakeholder engagement in co-creation processes for innovation: a systematic literature review and case study - Loureiro, S. M. C.; Romero, J.; Bilro, R. G. (Journal of Business Research, 2020)
Companies need to enhance corporate performance by stimulating the links between stakeholder engagement, innovation, and co-creation. Previous literature lacks a systematic and integrative conceptualisation of these factors, limiting our understanding of how to leverage stakeholders in innovation and co-creation strategies. Based on a systematic literature review (112 papers), this paper presents a discussion on the conceptualisations of stakeholder engagement, open innovation, and co-creation, compiles research gaps and further research directions, and propose a conceptual model for stakeholder engagement. The model is globally validated through a case study from 22 companies in the wine industry. Findings suggest jointly managing engagement in co-creation activities of internal and external stakeholders through several types of antecedents, accounting for engagement evolution across time. Among its limitations, this research excludes working papers under review and studies not in English. The model validation is circumscribed to ongoing co-creation processes involving internal stakeholders and distribution partners.